A novel study: long-lasting event memory. Issue 8 (14th September 2021) - Doolen, Abigail C.; Radvansky, Gabriel A.
ABSTRACT: The current study reports two experiments that assessed memory for complex sets of information (i.e., four novels) over the course of several years. This was done to explore several issues, including (a) the content and durability of memory, (b) causal connectivity among the described events, (c) serial position within the novel, (d) pattern of retention and forgetting, and (e) interest in the novel. This study revealed that people remember events read in a novel for long periods of time with a shallow rate of forgetting. We also found that they remembered information better when it was presented earlier on in the novel, was more causally connected to other events in the novel, and was transitional in the character or story plot. Consistent with prior research, reported level of interest was not related to later memory. Because we experience events through different learning modalities (e.g., novels, film, autobiographical experience) which are likely remembered similarly, this research broadens our understanding of how people remember the events they learn about through different means.